Achieving superior ductility for laser solid formed extra low interstitial Ti-6Al-4V titanium alloy through equiaxial alpha microstructure. (15th March 2018) - Zhao, Zhuang; Chen, Jing; Tan, Hua; Zhang, Guohao; Lin, Xin; Huang, Weidong
Abstract: The limited ductility of laser solid formed (LSFed) titanium alloy is a critical issue, which hinders their potential engineering applications. Here, we reported a largely improved ductility (25.1% total elongation) of LSFed extra low interstitial Ti-6Al-4V titanium alloy with a comparable tensile strength (> 860 MPa, international standards) using triple heat treatment. Superior ductility was mainly attributed to the gradual globularization of the α laths during subcritical annealing. The secondary α lamellar obtained by the solution treatment and aging was responsible for the tensile strength. The present findings provide significant guidance for fabricating LSFed titanium alloy having high ductility and good strength. Graphical abstract: Image 1